Analisis Pengaturan Hukum atas Perbuatan Pengambilan Paksa Kendaraan Fidusia oleh Debt Collector - Dhany, Rahmat; Zulfiko, Riki (Universitas Pahlawan Tuanku Tambusai, 2024)
This study provides an overview of the Criminal Act of Confiscation committed by Debt Collectors against customers who are in arrears. This criminal act causes customers to feel disadvantaged and humiliated because it occurs in a school environment. To find out the extent of the responsibility of debt collectors who commit criminal acts by confiscating vehicles that have problematic credit. The formulation of the problems raised 1) How is the regulation of vehicle confiscation on the highway carried out by debt collectors based on positive Indonesian law, 2) How is the criminal responsibility for confiscation of two-wheeled motor vehicles on the highway carried out by debt collectors against customers who are in arrears The method used in this study is normative research, where this research can be carried out by means of literature research, so that it can answer the formulation of the problem in accordance with the author's title.